2019
DOI: 10.2147/ahmt.s185041
|View full text |Cite
|
Sign up to set email alerts
|

<p>Mobile phone, social media usage, and perceptions of delivering a social media safer sex intervention for adolescents: results from two countries</p>

Abstract: Purpose: Rates of sexually transmitted infections among adolescents remain high in the United States and Botswana. Mobile phone density rates in Botswana exceed those of the United States. Yet, in both countries, safer sex information continues to be delivered primarily via face-to-face curricula such as Becoming a Responsible Teen and Living as a Safe Teen . While social media shows promise as a medium for delivering risk-reduction information to youth,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
2
15
0
1
Order By: Relevance
“…For mobile owners compared to non-owners, the odds of having a comprehensive knowledge of HIV instead of low to moderate knowledge of HIV was higher by more than 27%. This finding is similar to the study done on adolescents from the United States and Botswana, where adolescents who discussed peer pressure and connectedness with mobile phones and social media had a general knowledge of Sexually Transmitted Infections (STIs) and HIV [ 38 ]. On the other hand, studies from Ghana, Uganda, and the United States elucidated that mobile phone usage among youths is useful for delivering HIV related information and HIV prevention [ 36 , 37 , 39 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For mobile owners compared to non-owners, the odds of having a comprehensive knowledge of HIV instead of low to moderate knowledge of HIV was higher by more than 27%. This finding is similar to the study done on adolescents from the United States and Botswana, where adolescents who discussed peer pressure and connectedness with mobile phones and social media had a general knowledge of Sexually Transmitted Infections (STIs) and HIV [ 38 ]. On the other hand, studies from Ghana, Uganda, and the United States elucidated that mobile phone usage among youths is useful for delivering HIV related information and HIV prevention [ 36 , 37 , 39 ].…”
Section: Discussionsupporting
confidence: 86%
“…This could be due to differences in access to mass media between urban and rural youths which play a very vital role in disseminating HIV-related educations and awareness creations. This study and other studies [18,[29][30][31][32][33][34][35][36][37][38][39] depicted that exposure to mass media is associated with acquiring comprehensive HIVknowledge.…”
Section: Discussionsupporting
confidence: 66%
“…Of the 231 100 new HIV infections reported in SA in 2017, youth (15–24 years) contributed to the majority (38%) of new HIV infections in 2017 [ 3 ]. Youth often engage in sexual activities without using a condom [ 3 , 4 ], have multiple sexual partners [ 5 ], and early sexual debut [ 3 , 6 ] that place them at high risk for HIV. Despite their high risk behaviour, youth often perceive low vulnerability to HIV [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Youth often engage in sexual activities without using a condom [ 3 , 4 ], have multiple sexual partners [ 5 ], and early sexual debut [ 3 , 6 ] that place them at high risk for HIV. Despite their high risk behaviour, youth often perceive low vulnerability to HIV [ 6 ]. Partly for this reason, utilisation of HIV testing remains low among this population and a high proportion of youth are not aware of their HIV status [ 5 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social media shows promise in the dissemination of mobile health information. A recent focus group with Botswana teens indicated that using social media to disseminate health promotion information about safer-sex practices is feasible and acceptable [8]. To date, social media interventions have focused on population health, [9] smoking cessation awareness [10], weight reduction [11], and behavior change among college students [12].…”
Section: Introductionmentioning
confidence: 99%